ANALISIS PERILAKU PENGENDARA DAN JARAK PANDANG HENTI SEPEDA MOTOR MATIC - Erika Buchari; Ahmad Gilang Dwi Junanta (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2018)
The growth of Matic-Motorcycle in Indonesia is increased steeply lately. According to Assosiasion of Indonesian Motorcycle Industry, AISI the sales of matic motorcycle have achieved 75,49% (3,639,000) of the wholesaler 4,821,000. In fact, motorcycle users do not realize that automatic motorcycle’s characteristics especially braking distance are different with those of non-automatic motorcycles. The different way of riding can cause uncontrolled vehicles during braking, when promptly change speed either faster or slower. Stopping sight distance is the distance needed by riders in order to stop their moving vehicles after seeing the obstacles in the front. This research is seeking to know the behavior of motorcycle users and stopping sight distance that is ideal for the users of automatic motorcycles. Multi linear Regression model is made to find out the relationship between stopping sight distance and other variables such as speed, machine capacity, type of brakes etc. From this model, it can be derived the ideal stopping sight distance which is affected by speed, machine capacity, type of front brakes. Perkembangan sepeda motor matic di Indonesia mengalami pertumbuhan yang sangat pesat beberapa tahun belakangan ini. Menurut data dari asosiasi industri sepeda motor Indonesia( AISI,2015) penjualan sepeda motor matic mengalami pertumbuhan yang sangat pesat dibandingkan dan motor bebek dan sport, yaitu 75,49% (3,639 juta matic dari penjualan 4,821 juta motor keseluruhan). Fakta di lapangan, pengguna tidak menyadari beda karakteristik kendaraan motor matic dengan non matic. Perbedaan ini mengakibatkan tidak terkontrolnya kecepatan kendaraan dimana seringnya terjadi perubahan percepatan dan perlambatan pada kendaraan tersebut. Jarak pandangan henti adalah jarak yang dibutuhkan oleh pengendara untuk menghentikan kendaraannya yang bergerak setelah melihat adanya rintangan pada lajur jalannya. Penelitian ini ingin mengetahui perilaku pengendara dan jarak pandang henti yang ideal bagi pengendara sepeda motor matic. Model Multi linear Regression hubungan Jarak pandangan henti dengan variable kecepatan, kapasitas mesin dan jenis rem diteliti. Hasilnya diperoleh jarak henti ideal yang dipengaruhi oleh kecepatan, kapasitas mesin, dan jenis rem depan.